2010
DOI: 10.1002/jcp.22394
|View full text |Cite
|
Sign up to set email alerts
|

Induction of small G protein RhoB by non‐genotoxic stress inhibits apoptosis and activates NF‐κB

Abstract: It has been reported by us and other groups that the expression of small GTP binding protein RhoB can be induced by genotoxic stressors and glucocorticoid (GC), a stress hormone that plays a key role in stress response. Until now stress-induced genes that confer cytoprotection under stressed conditions are largely unknown. In this study, we investigated the effects and mechanism of non-genotoxic stressors, including scalding in vivo and heat stress in vitro on the expression of RhoB. We found for the first tim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
15
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 54 publications
2
15
0
Order By: Relevance
“…RhoB is the only member of Rho GTPase family of proteins that is rapidly and transiently upregulated in response to stress conditions 12,47 and our results show that increased RhoB activity has a protective effect on pulmonary vascular cells under conditions of limited oxygen supply. Establishing upstream activators of RhoB will require further studies.…”
Section: Discussionmentioning
confidence: 54%
“…RhoB is the only member of Rho GTPase family of proteins that is rapidly and transiently upregulated in response to stress conditions 12,47 and our results show that increased RhoB activity has a protective effect on pulmonary vascular cells under conditions of limited oxygen supply. Establishing upstream activators of RhoB will require further studies.…”
Section: Discussionmentioning
confidence: 54%
“…The p38 pathway has been particularly linked to the promotion of increased mRNA stabilization of numerous inflammatory genes, such as IL-1, IL-6, IL-8, VEGF, TNFα, and COX-2 [4]. Our previous study showed that p38 pathway is involved in heat stress-induced RhoB expression in human lung carcinoma cell line A549 [19]. In the present study, we found that Dex can activate Akt and p38 in MG-63 cells.…”
Section: Discussionmentioning
confidence: 99%
“…RhoB is involved in endocytosis and vesicle trafficking, it therefore contributes to the cytoplasmic membrane targeting of a variety of receptors and signalling molecules such as epidermal growth factor receptor, platelet‐derived growth factor receptor, non‐receptor kinases src and Akt in cells . RhoB can be rapidly up‐regulated by cytokines or growth factors, such as TGF‐β and be activated by genotoxic stress and heat stress . It is considered a stress sensor and plays an important role in the regulation of cytoskeletal organization, cell proliferation, cell survival and tumour invasiveness .…”
Section: Introductionmentioning
confidence: 99%